Impact of the implementation of a new information system on the pharmaceutical supply chain - berdi, Fadoua; Ennefah, Wafaa; Ifezouane, Jihane; Elwartiti, Mohammed Adnane; Bennana, Ahmed; Lamsaouri , Jamal (Jour Med Resh and Health Sci, 2021)
Introduction: The hospital pharmacy information system optimizes the operation of the various stakeholders. It would be essential to have a system capable of controlling the entire pharmaceutical supply chain and therefore optimizing expenses. The objective of our work was to assess the supply chain before and after the implementation of the information system allowing a connected prescription. Materiel and methods: The study was carried out in two parts, a survey before the implementation of the connected prescription and another four months after the implementation of the new system. The two questionnaires were intended for staff responsible for pharmacy at the service level. They were carried out based on a review of the literature on pharmaceutical logistics and on quality at the hospital pharmacy level. Results: The frequency of requests sent to the pharmacy varied between once a week by 3% of departments before the new information system and 28% after the installation of the computer system, twice a week by 61% of departments before the system and 6% after. the time to prepare a request was more than an hour for 72% of the services, after the new system this time was reduced to less than 30 minutes for 34% of the services. The quality of the pharmacy service was rated very satisfactory by 39%. Discussion: The implementation of the new system made it possible to better manage stocks and avoid leaks with rigorous monitoring. The time between the request and the collection of products from the pharmacy has been shortened. The main objective of an information system is to save time, reduce prescription errors, reduce incomplete prescriptions and reduce peaks in activity. The assessment of the quality of the service offered by the pharmacy depends on several parameters, including human resources and the rate of breaks. Conclusion: While computerization remains a very useful tool, its proper functioning depends on the commitment of all users.